Analisis Efektivitas Peran Departemen Portofolio Bisnis PT GP Dalam Mengevaluasi Kinerja Entitas Anak - Syafia Maharani; Fajar Syaiful Akbar (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This article will discuss the effectiveness of the role of the PT GP Business Portfolio Department in evaluating the performance of subsidiaries. The research method used is descriptive qualitative by conducting interviews, observation and document analysis. The results show that the Business Portfolio Department not only plays an effective role in analyzing the financial performance of subsidiaries. However, it acts as an information bridge between the subsidiary and the parent entity. So, in general, the role of the Business Portfolio Department is said to be effective in preventing companies from experiencing business merger failure